Research trends in methods for controlling macro-micro motion platforms - Lufan Zhang; Pengqi Zhang; Boshi Jiang; Heng Yan (Nanotechnology and Precision Engineering, 2023)
With ongoing economic, scientific, and technological developments, the electronic devices used in daily lives are developing toward precision and miniaturization, and so the demand for high-precision manufacturing machinery is expanding. The most important piece of equipment in modern high-precision manufacturing is the macro-micro motion platform (M3P), which offers high speed, precision, and efficiency and has macro-micro motion coupling characteristics due to its mechanical design and composition of its driving components. Therefore, the design of the control system is crucial for the overall precision of the platform; conventional proportional–integral–derivative control cannot meet the system requirements, and so M3Ps are the subject of a growing range of modern control strategies. This paper begins by describing the development history of M3Ps, followed by their platform structure and motion control system components, and then in-depth assessments of the macro, micro, and macro-micro control systems. In addition to examining the advantages and disadvantages of current macro-micro motion control, recent technological breakthroughs are noted. Finally, based on existing problems, future directions for M3P control systems are given, and the present conclusions offer guidelines for future work on M3Ps.